DegS protease regulates antioxidant capacity and adaptability to oxidative stress environment in Vibrio cholerae - Wang, Kaiying; Lu, Huifang; Zou, Mei; Wang, Guangli; Zhao, Jiajun; Huang, Xiaoyu; Ren, Fangyu; Hu, Huaqin; Huang, Jian; Min, Xun (Frontiers in Cellular and Infection Microbiology, 2023)
Adaptation to oxidative stress is critical for survival of Vibrio cholerae in aquatic ecosystems and hosts. DegS activates the σE envelope stress response. We have previously revealed that DegS may be involved in regulating the oxidative stress response. In this study, we demonstrated that deletion of the degS gene attenuates the antioxidant capacity of V. cholerae. In addition, our results further revealed that the regulation of antioxidant capacity by DegS in V. cholerae could involve the cAMP-CRP complex, which regulates rpoS. XthA is an exonuclease that repairs oxidatively damaged cells and affects the bacterial antioxidant capacity. qRT-PCR showed that DegS, σE, cAMP, CRP, and RpoS positively regulate xthA gene transcription. XthA overexpression partially compensates for antioxidant deficiency in the degS mutant. These results suggest that DegS affects the antioxidant capacity of V.cholerae by regulating xthA expression via the cAMP-CRP-RpoS pathway. In a mouse intestinal colonization experiment, our data showed that V.cholerae degS, rpoE, and rpoS gene deletions were associated with significantly reduced resistance to oxidative stress and the ability to colonize the mouse intestine. In conclusion, these findings provide new insights into the regulation of antioxidant activity by V.cholerae DegS.